Major importance of 'minor' resources : women and plant biodiversity - Howard, Patricia (International Institute for Environment and Development LondonGB, 2003)
Describes how women predominate in plant biodiversity management in their roles as housewives, plant gatherers, homegardeners, herbalists, seed custodians and informal plant breeders. Looks at how gender bias affects scientific knowledge of the plant world and how this in turn affects our ability to shape that world in ways that we desire.\n